Fluorine-doped material for functional coatings on lithium-based batteries
Patent Information
- Application Number
- CN202580023474.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-22
- Filing Date
- 2025-03-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]然而,锂电池通常可能遭遇若干导致性能衰减甚至失效的问题
[0010]与其他大多为绝缘性的ALD沉积氧化物涂层材料(包括氧化铝、氧化锆及二氧化硅)相比,本研究具备的显著优势包括:提供拥有优异电子-离子混合电导率的混合导电阻挡涂层。该方案可实现便于锂离子传输的功能涂层,同时缓解潜在的电池安全及稳定性问题。
Smart Images

Figure CN122996518A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to lithium batteries. Background Technology
[0002] To achieve widespread energy utilization, lithium batteries, known for their high energy density, have become a key energy storage system for overcoming the challenges of limited energy resources and space constraints.
[0003] However, lithium batteries often encounter several problems that can lead to performance degradation or even failure. These problems include: adverse reactions between the electrodes and electrolytes, forming transport barrier layers, namely the so-called SEI (solid electrolyte interface) at the anode and the so-called CEI (cathode electrolyte interface) at the cathode; dissolution of transition metal ions; oxygen evolution, which poses fire and safety risks; and structural degradation and pulverization caused by the repeated insertion and extraction of lithium ions during battery cycling. Although solid electrolytes have attracted attention due to their potential to solve safety issues, they may still encounter similar obstacles, including low ionic conductivity.
[0004] To overcome these challenges, the application of functional coatings becomes essential, as they can provide the necessary electrochemical, chemical, and structural stability to active materials. However, such coatings may also increase resistive losses.
[0005] Functional coating materials deposited on the surface of the active electrode of a lithium battery can suppress calendar aging, as well as chemical degradation, electrochemical degradation, and structural degradation during battery cycling, such as SEI / CEI formation and dendrite formation.
[0006] However, such coating materials may also have undesirable properties, such as parasitic voltage drop and poor lithium-ion transport capabilities. Therefore, providing a lithium-ion battery electrode barrier layer with improved performance would be an advancement in this field. Summary of the Invention
[0007] Among a range of coating technologies, including pulsed laser deposition, sol-gel coating, and radio frequency magnetron sputtering, atomic layer deposition (ALD) stands out due to its superior uniformity and conformality. ALD allows for precise control of coating thickness at the atomic scale and achieves the desired stoichiometric composition.
[0008] This study provides an ALD growth composition (i.e., fluorine-doped ALD-grown ternary lithium oxide) for functional coating materials, which exhibits significant electron-ion mixed conductivity, making it different from most similar coatings reported to be made primarily of electronically insulating oxide materials.
[0009] This research can be applied to multiple areas of the battery industry that require the protection of battery electrodes from parasitic reactions and degradation effects by providing a thin and uniform physical barrier layer, combined with the advantageous properties of electron-ion hybrid conductivity. Furthermore, this research is suitable for applications where battery electrode safety and stability are paramount.
[0010] Compared to other mostly insulating ALD (alloy deposition) oxide coating materials (including alumina, zirconium oxide, and silicon dioxide), this study offers significant advantages, including providing a hybrid conductive barrier coating with excellent electron-ion mixed conductivity. This approach enables functional coatings that facilitate lithium-ion transport while mitigating potential battery safety and stability issues. Attached Figure Description
[0011] Figures 1A to 1C Various barrier layer configurations are shown.
[0012] Figure 1D An exemplary embodiment of the present invention is shown.
[0013] Figure 2A -B shows the calculated effect of fluorine doping on the density of states.
[0014] Figure 3A -B is a TEM image of the fluorine-doped barrier layer grown by ALD.
[0015] Figure 4A -B shows the effect of fluorine doping on conductivity.
[0016] Figure 5A This example demonstrates the optimal fluorine doping level.
[0017] Figure 5B This is the Arrhenius plot, which compares LMO with a fluorine-doped LVO layer on its surface with bare LMO.
[0018] Figure 6 The calculated energy barriers for lithium-ion transport are shown for undoped LVO and two different levels of LVO. Detailed Implementation
[0019] Part A describes the general principles involved in the embodiments of the present invention. Part B describes several related experiments in detail.
[0020] A) General Principles
[0021] An exemplary embodiment of the present invention is a lithium battery comprising: an anode, a cathode, an electrolyte, and a barrier layer disposed on at least one of the cathode and the anode. The barrier layer comprises a ternary lithium oxide grown by ALD (atomic layer deposition), wherein the ALD-grown ternary lithium oxide is doped with fluorine during the ALD growth process.
[0022] The barrier layer preferably allows lithium-ion transport, for example, having a density of 10... -6 Ionic conductivity in the range of S / cm to 10² S / cm.
[0023] The barrier layer preferably has a mixed conductivity provided by both electrons and ions, for example, having a conductivity of 10. -8 Electronic conductivity in the range of S / cm to 10² S / cm (more preferably greater than 10) -5 S / cm), preferably having the same properties as 10 -6 Ionic conductivity in the range of S / cm to 10²S / cm.
[0024] Compositions suitable for the ternary lithium oxides grown in the ALD include Li-MO compositions, wherein M is Ti, Nb, V, W, Mn, Mo, Ta, La, Co, or Ni. More broadly, cathode or anode materials that enable one-dimensional, two-dimensional, or three-dimensional lithium-ion transport through their lattice can serve as suitable barrier materials. Suitable barrier materials may have Li-MO compositions, wherein M is a transition metal having more than one oxidation state. Such materials, upon fluorine doping, can generate lithium-ion vacancies in their crystal structure, which facilitate the smooth insertion of lithium ions from (and / or to) the electrolyte.
[0025] Generally, the barrier layer considered in this application can protect the cathode and / or anode through a variety of mechanisms, including acting as a physical barrier layer and acting as an artificial solid interface. The implementation of this invention does not critically depend on the above-described mechanisms.
[0026] The barrier layer may be disposed on the cathode and / or on the anode.
[0027] The fluorine atomic fraction of the ternary lithium oxide grown by ALD is preferably from 0.5 atomic% (at%) to 6 atoms, more preferably from 1 atomic% to 3 atoms. The ternary lithium oxide grown by ALD can be deposited by repeated ALD cycles, including lithium fluoride sub-cycles sandwiched between lithium vanadate sub-cycles, to provide fluorine doping.
[0028] The thickness of the barrier layer is preferably in the range of 3 nm to 20 nm.
[0029] Suitable cathode material compositions include, but are not limited to: LiMn2O4 (spinel), LiFePO4 (olivine), LiCoO2 (layered), and LiNi. x Mn y Co z O2 (layered). The barrier layer used for the cathode can prevent the formation of a blocking cathode electrolyte interface (CEI) and replace the interface with a barrier layer that has both electronic and ionic conductivity. The barrier layer can allow lithium-ion transport and electron transport with minimal voltage loss, suppress parasitic side reactions with the electrolyte, prevent transition metals from dissolving from the cathode, and avoid oxygen evolution.
[0030] Suitable anode material compositions include, but are not limited to: silicon, graphite, and Li4Ti5O. 12 And lithium metal. The main purpose of the barrier coating used for the anode is to prevent the formation of a blocking solid electrolyte interface (SEI) and instead provide the anode with a barrier layer that has both electronic and ionic conductivity, allowing lithium-ion and electronic transport to pass through with minimal voltage loss, while preventing dendrite formation at the anode.
[0031] Suitable electrolyte compositions include, but are not limited to: LiPON and Li7La3Zr2O 12 The electrolyte is preferably a liquid or solid electronic insulator with an ionic conductivity of 10. -8 S / cm to 10 -1 Within the range of S / cm.
[0032] B) Specific Examples
[0033] This section provides several examples of the aforementioned concepts.
[0034] B1) Introduction
[0035] There is an urgent need to develop effective barrier coatings to mitigate and minimize the degradation of electrode materials in lithium-ion batteries (LIBs). These barrier coatings are expected to improve the electrochemical, chemical, and structural stability of the active materials in battery components. More specifically, the coating can act as a physical barrier layer, effectively isolating the electrode from the electrolyte to prevent parasitic reactions, thereby stabilizing the electrode surface. Extensive research activity reflected in numerous published documents and reports confirms the industry's high level of interest in finding the most effective protective coating materials and their optimal preparation methods. The coating needs to be stable, able to uniformly and conformally cover the electrode surface down to the particle level, and must be sufficiently conductive and thin to minimize voltage loss caused by the coating's additional ohmic resistance. In other words, such coatings may constitute additional barriers to lithium-ion and electron transport, and their resistance may be significantly higher than that of the electrode active materials. Therefore, ensuring smooth electron and lithium-ion conduction within the barrier coating is crucial, as this directly affects the cell's properties and performance, including its capacity and calendar life.
[0036] The core of this study is to use ALD (Atomic Layer Deposition) as a representative coating method to provide general guidance for uniformly mixed conductive coatings. Among various coating techniques applicable to LIBs (including various wet chemical methods, pulsed laser deposition, and RF magnetron sputtering), ALD can not only achieve the directional implementation of intrinsic doping strategies, but also provide excellent uniformity and conformal coverage. This contrasts sharply with most traditional coating methods, which often leave unprotected areas exposed to the same degradation mechanisms, potentially leading to severe capacity decay.
[0037] It is important to emphasize that the functional coating should be of mixed conductivity. In other words, it should not only facilitate heterogeneous charge transfer but also provide favorable pathways for electron and lithium-ion conduction. Lithium ions in the electrolyte require not only lithium-ion vacancies but also electrons to embed in the coating while maintaining charge neutrality on both sides of the interface. The lack of these defects in insulating oxide coatings can disrupt the charge balance during charge and discharge, potentially leading to lithium-ion accumulation at the coating-electrolyte interface. Such charge separation and polarization can adversely affect electrochemical performance. To maintain charge neutrality and achieve effective bipolar diffusion across the barrier coating, electron transfer must be balanced with lithium-ion transport from the electrolyte. The importance of mixed conductivity is further highlighted when a uniform and conformal coating is applied via ALD, while its importance may have been previously underestimated in scenarios with uneven or incomplete coverage. For the coating to achieve its intended function, it must be thin enough to avoid additional resistive losses while being thick enough to avoid pinholes and uniformly and conformally covering the electrode surface.
[0038] However, most coating technologies are prone to uneven or incomplete surface coverage, often resulting in exposed areas, and lack sufficient control over the thickness, uniformity, and conformality of the protective coating. Figures 1A to 1C This situation is illustrated in the accompanying figures, which compare the behavior of discontinuous insulating barrier coatings, continuous insulating barrier coatings, and hybrid conductive barrier coatings, based on the preset mechanism of lithium ion embedding into the lower cathode material.
[0039] More specifically, Figures 1A to 1C The possible paths for lithium ions to embed from the liquid electrolyte 104 into the cathode barrier layer and their corresponding voltage curves are schematically compared. Figure 1A As shown, for the discontinuous insulating coating 106, lithium ions in the electrolyte 104 can easily contact the exposed surface of the cathode 102 to achieve smooth embedding, but in the cathode portion covered by the blocking coating, lithium ions can only be embedded through the grain boundaries. Figure 1B As shown, for the continuous insulating coating 108, lithium ions in the electrolyte 104 can only be embedded into the underlying LMO (lithium manganese oxide) cathode 102 through cracks and grain boundaries in the barrier layer 108. The insulating coating prevents lithium ions from directly and integrally embedding into the lattice sites of the barrier layer from the electrolyte. Figure 1C As shown, for the electron-ion hybrid conductive coating 110 (e.g., the fluorine-doped LVO proposed in this study), the lithium-ion vacancies formed by fluorine doping can promote the insertion of lithium ions from the electrolyte.
[0040] Figure 1D The illustration shows items such as Figure 1C The battery shown has a barrier layer 110. Here, 102 is the cathode, 104 is the electrolyte, 110 is the barrier layer, 112 is the anode, and 114 is an optional second barrier layer on the anode.
[0041] The schematic voltage distribution expected for various cathode coating methods is also... Figure 1A -C is shown. Figure 1A The discontinuous coating depicted in the figure provides only limited protection by blocking part of the active cathode surface from parasitic reactions. Figure 1B The electronically insulating and uniformly covering coating is expected to result in a significant voltage drop, which naturally leads to a decrease in battery potential. However, in contrast, as... Figure 1C As shown, due to the high electronic conductivity of the hybrid conductive barrier layer, there is almost no voltage loss across the hybrid conductive barrier coating—except for a very small resistance loss.
[0042] Various wide-bandgap oxides and several lithium ternary oxides have been reported in the literature as barrier coatings, including ZrO2, Al2O3, ZnO, and Li3PO4. While electronically insulating monovalent oxides provide an ideal chemical barrier to reduce the tendency for harmful side reactions, they also provide a physical barrier for lithium-ion intercalation at the oxide coating / electrolyte interface. Figure 1A -B). These highly insulating oxide coatings with monovalent cations lack a charge compensation mechanism, preventing lithium ions from the electrolyte or cathode from easily embedding into the oxide lattice. This embedding reaction can be represented as...
[0043] In the absence of electronic defects in the coating material for charge compensation, this reaction must overcome a significant energy barrier to proceed. Therefore, lithium ions in the electrolyte are likely to enter the underlying cathode material through microcracks and grain boundaries in the coating. As an example of a monovalent oxide, there are reports of ALD in LiNi... 0.5 Mn 1.5 Al₂O₃ deposition on O₄ particles promotes capacity retention, but increased coating thickness leads to capacity loss due to impeded electron and lithium-ion transport. Compared to these oxides, Li incorporation in the coating material improves ionic conductivity. However, lithium ternary oxides may lack sufficient electronic conductivity due to their typically wide bandgap, and generally exhibit lower ionic conductivity than cathode active materials. For example, another study reported an ionic conductivity of 5.6 for a lithium aluminate (LiAlO₂) coating at room temperature. 10 -8 S cm -1 And successfully protected LiNi 0.5 Mn 1.5 O4 is protected from potential side reactions. It has also been reported that the lithium phosphate (Li3PO4) coating has an ionic conductivity of 4.3 at room temperature. 10 -6 S cm -1 .
[0044] In contrast to these highly insulating oxides, this work instead utilizes mixed ion-electron conductivity (MIEC) doped oxides as effective cathode blocking coatings via ALD. A systematic fluorine (F) doping strategy is introduced into the anionic sublattice of the oxide structure to generate lithium vacancies (…). Anion doping can generate bonding environments with varying charge densities and provide variations in local spatial distribution, thereby affecting the activation barrier for lithium-ion transport. In particular, fluorine doping is known to contribute to the formation of rigid structures and reduce the lattice constant, thus affecting lithium storage capacity. The higher vacancy concentration resulting from fluorine doping not only lowers the activation barrier for lithium-ion intercalation but also increases lithium-ion conductivity. Similarly, fluorine doping, as an effective donor, may partially lead to electronic transitions in the oxidation states of multivalent cations used for charge compensation, resulting in increased electronic conductivity of the parent oxide material.
[0045] This coating strategy differs from traditional insulating oxide coatings in several important ways. First, this study utilizes lithium vanadate (LVO), particularly LiVO3, as the F-doped ion-conducting host structure to achieve enhanced mixed conductivity. LiVO3 is a wide bandgap semiconductor material with a bandgap typically around 3.1 eV, making it unsuitable as an electrode material unless intrinsically doped to simultaneously improve both ion and electron transport properties.
[0046] Secondly, this study employs a doping strategy to generate lithium-ion vacancies ( This process simultaneously promotes lithium-ion transport and improves electronic conductivity. The coating material introduces fluorine doping into the oxygen sublattice through a lithium fluoride (LiF) ALD subcycle. It has an effective charge of +1. The charge neutrality of the coating material is achieved through... The generation and maintenance of this defect. In Kröger-Vink notation, this defect response can be represented as,
[0047] The increased concentration of lithium-ion vacancies induced by fluorine doping can improve charge transport across the protective coating. Simultaneously, it promotes the incorporation of lithium ions from the electrolyte (or cathode) into the protective layer, as illustrated by the defect reaction below.
[0048]
[0049] Finally, the optimal F doping concentration in the LVO main structure was thoroughly investigated by adjusting the ALD sub-cycle ratio of LVO and LiF. Experimental studies, supported by theoretical calculations, show that an ideal F doping concentration exists, and the optimally doped LVO exhibits the highest mixed conductivity.
[0050] This work reports important findings on the feasibility and advantages of fluorine-doped electron-ion hybrid conductive coatings for cathode protection of lithium-ion batteries.
[0051] B2) Results and Discussion
[0052] Figure 2A The calculated PDOS (projected density of states) of the optimized LiVO3 1×1×3 supercell structure is shown. Figure 2B The optimized LiVO4 obtained by density functional theory calculation is shown. 3-y F y Calculated PDOS of a 1×1×3 supercell structure.
[0053] The advantages of fluorine doping in host lithium ternary oxides, such as in LVO3, can be predicted first by DFT calculations, which reveal a significant reduction in band gap. First, LiVO3 and LiVO3 were constructed and optimized. 3-y F y Supercell. The substitution of a single F atom at an O site represents 1.7 atomic% F doping in the LVO host structure. In the monoclinic LiVO3 structure, the LiO6 octahedron and VO4 tetrahedron share vertices. The substitution of a single F atom disrupts the shared-vertices bonding environment, shortening its bond length with Li from 2.05 Å to 1.94 Å, while lengthening its bond length with V from 1.64 Å to 1.98 Å. This bond reconstruction can induce electronic localization. This change in bond length may affect the electron density distribution, resulting in ionic bonds with localized electrons between Li and F. These localized electrons are expected to be electrostatically favorable for lithium-ion transport in the host structure, resulting in enhanced lithium-ion conductivity. The LiVO3 1×1×3 supercell structure exhibits a direct band gap of 3.1 eV, consistent with reported values in the literature. 3-y F y The band structure of the 1×1×3 supercell structure shows that the band gap between the conduction band top (CBM) and the valence band top (VBM) decreases significantly from 3.1 eV to 2.5 eV, with the Fermi level located near the CBM.
[0054] In addition to the enhanced electronic conduction results obtained from band structure analysis, PDOS analysis revealed that the substitution of oxygen atoms by F atoms led to perturbations of the electronic states of adjacent vanadium sites. Figure 2A and Figure 2B The original LiVO3 and LiVO3 are shown respectively. 3-y F y The PDOS structure. Compared with the original LiVO3 structure, LiVO3... 3-y F y The PDOS of the structure is more pronounced at the Fermi level and exhibits metallic properties. This indicates that the additional electronic states near the Fermi level lead to a significant increase in electronic conductivity. As shown in more detailed simulations, LiVO 3-y F yThese new electronic states near the Fermi level in the structure originate from the hybridization between vanadium d orbitals and oxygen p orbitals; most of the electronic states of F lie below the Fermi level. More specifically, LiVO 3-y F y In the structure, the tetrahedral e-states and t2-states of VO4 split into these new electronic states in the conduction band. Compared to the original LiVO3, the e- and t2 symmetries of VO4 are perturbed by F substitution. and The splitting of the e-state of the orbit, and with , and The splitting of the t2 state of the orbit leads to a new energy state near the Fermi level.
[0055] Doping with a single F atom further reduces the lithium vacancy formation energy. The defect formation energy as a function of the Li chemical potential was studied within the known electrochemical stability range of cathode materials. The lithium vacancy formation energy was reduced by 2 eV due to 1.7 atomic% F doping in the LiVO3 supercell structure. This reduced lithium vacancy formation energy is closely related to the initiation of vacancy-mediated transport.
[0056] B2a) Structural and compositional analysis
[0057] In the previous section, band structure and PDOS analysis showed the importance of F doping for enhanced charge transfer, which inspired the introduction of F doping into coating materials.
[0058] To prepare LVO-F films with different F concentrations, LiVO4 was used. x Different ALD subcycle ratios (a:b) for LiF were used. XPS (X-ray photoelectron spectroscopy) was performed to quantify the surface-specific atomic percentages (F%) of pristine LVO and LVO-F films. XPS F1s spectra of LVO-F films with different a:b ratios showed that F atoms were systematically controlled within the LVO host structure. The F1s peak at 685 eV was identified as Li-F bonding. For pristine LVO films, no significant XPS F1s peak was observed. The peak area of the F1s spectrum was proportional to the number of LiF subcycles, indicating that higher LiF subcycle frequencies increased F doping concentration. F atoms ranged from 0.7% to 3.8% at different ALD subcycle ratios (a:b). The LVO-F-616 film exhibited the lowest F concentration of 0.7%, followed by the LVO-F-313 film with a higher F concentration of 1.9%, corresponding to the doping concentration in band structure and PDOS analysis. In addition to the F1s spectrum, an increase in the atomic percentage ratio of Li relative to V was observed, attributed to a higher count of LiF subcycles while the total number of LiVOx subcycles remained constant. The V2p of the LVO-F-313 thin film... 3 / 2The spectrum may be deconvolved into two distinct valence states V. 5+ and V 4+ Their binding energies are 517.3 eV and 516.1 eV, respectively. 4+ The presence of valence states may be attributed to single-atom argon sputtering used to remove carbon contamination from the thin film surface.
[0059] Figure 3A The image shows a transmission electron microscope (TEM) image of LiMn2O4(LMO) particles coated with LVO-F-313. Figure 3B High-magnification TEM image of LMO particles coated with LVO-F-313.
[0060] exist Figures 3A-3B The HRTEM images further reveal a conformal and homogeneous LVO-F-313 coating containing 1.9% F, representative of the LVO-F coating, applied to LMO. Aberration-corrected scanning TEM (STEM) images equipped with a high-angle annular dark-field (HAADF) detector further confirm the conformal LVO-F-313 coating. This also clarifies the interface between the coating and the electrode particles, as well as the energy-dispersive spectral (EDS) mappings of V, O, F, and Mn. Because the LVO-F-313 is three-dimensionally coated on the particles and also on the TEM grid, low signals of V, O, and F can be observed on the outer side of the particles.
[0061] B2b) Electrical performance
[0062] Figure 4A The room temperature conductivity measurements of pristine LVO and LVO-F-313 films prepared on the hPSi platform are shown. Figure 4B Arrhenius diagram of the original LVO and LVO-F-313 films prepared on the hPSi platform.
[0063] The electrical properties of the LVO-F coating were investigated using the hPSi platform. The conductivity of the pristine LVO and LVO-F-313 films was compared in parallel with the DFT calculations performed under the 1.7 atom% F doping condition described in the previous section. Figure 4A As shown, a significant difference of approximately three orders of magnitude in conductivity was observed between the two compositions at room temperature. The room temperature conductivity of LVO and LVO-F-313 films was 2.6. 10 -9 S cm -1 and 1.2 10 -5 S cm -1 . Figure 4BThe activation energies for charge transport in pristine LVO and LVO-F-313 films are shown. The activation energy of pristine LVO, extracted from Equation 4, is 0.69 eV, highly consistent with the previously reported value of 0.7 eV. However, the activation energy of the LVO-F-313 film is only 0.11 eV, showing a significant decrease due to favorable F doping.
[0064] We noted that the charge transfer resistance reflects both electronic and ionic resistance. To support the concept of hybrid conduction, we performed DC conductivity measurements at room temperature. We found that the LVO-F thin film exhibits hybrid conductivity behavior with an electronic conductivity of approximately 10⁻⁶. -6 S·cm - ¹.
[0065] Figure 5A This is a resistivity plot of different F doping concentrations on the LMO(LiMn2O4) platform. Figure 5B It is an Arrhenius diagram of LVO-F-313 thin film on LMO and bare LMO.
[0066] The effect of hybrid conductive LVO-F coatings can be simulated by using LMO as an exemplary cathode material. We assume that there exists an optimal fluorine doping concentration to achieve the highest conductivity. Figure 5A The ASR values of LVO and LVO-F films on sputtered LMO surfaces are presented. These values were obtained at room temperature using charge transfer resistance measurements obtained via EIS. The ASR value is 7.5 Ω. cm 2 Starting with the original LVO thin film, the ASR decreases with the incorporation of 0.7 atomic% fluorine into the LVO structure. Notably, the ASR continues to decrease, reaching its minimum at a fluorine doping level of 1.9 atomic%, resulting in an ASR value less than 0.4 Ω. cm 2 However, beyond this optimal fluorine concentration, the ASR increases with increasing fluorine doping concentration. When the fluorine concentration exceeds 3%, the ASR of the LVO-F film even remains higher than that of the original LVO film. This may be attributed to the increased defect association that slows down transport, or to the formation of excessive Li-F bonds with electronic insulating properties.
[0067] The lowest ASR value from the LVO-F-313 film indicates enhanced conductivity, encompassing both electronic and lithium-ion conductivity. This distinguishes it from other reported ALD oxide films. The presence of this optimal F concentration highlights the importance of limiting the doping concentration within a specific range to obtain the highest mixed electronic and ionic conductivity. Within the LVO-F-313 structure with the optimal doping concentration, charge transport is likely to remain unimpeded because electronic localization induced by excess electrons from the F dopant may play a crucial role in the affinity for lithium ions. In contrast, when the doping concentration exceeds the optimal point, electrons become over-localized around the VO bonds, potentially forming electronic polarons and reducing conductivity.
[0068] To elucidate the advantages of the optimal LVO-F coating on the LMO platform, the charge transport activation energies of bare LMO and LVO-F-313 coated LMO were compared, such as... Figure 5B As shown. The conductivity of bare LMO at room temperature is 4 × 10⁻⁶. -8 The activation energy of bare LMO is consistent with values reported elsewhere. The charge transport activation energy is reduced by approximately 0.1 eV. We emphasize that the conductivity is reduced by more than three orders of magnitude. Combining the intrinsic electrical properties with the application of the optimal LVO-F coating on LIB cathode materials, we demonstrate that the optimal LVO-F coating not only exhibits enhanced mixed conductivity but also reduces the charge transfer resistance of LMO and promotes lithium-ion conduction.
[0069] B2c) Lithium-ion transport characteristics
[0070] To investigate at the atomic scale how F doping might affect lithium-ion transport within the LVO host structure, NEB calculations were performed. The substitution of a single O atom by F corresponds to a doping concentration of approximately 1.7 atomic percent, equivalent to the F concentration in the LVO-F-313 thin film.
[0071] Figure 6 The figure of Li calculated by density functional theory is shown. 1-x VO3, Li 1-x VO 3-y F y and Li 1-x VO 3-2y F 2y Energy distribution of lithium-ion transport in a supercell structure.
[0072] These calculations take Li into consideration 1-x VO3 and Li 1-x VO 3-ay F ay Several lithium-ion transport trajectories in the (a=1,2) structure. The trajectory closest to the doped F atom was selected to facilitate lithium-ion transport in Li.1-x VO3 and Li 1-x VO 3-ay F ay Transport within the supercell structure. Li 1-x VO 3-ay F ay The transport trajectory in the structure may deviate slightly from Li due to the relatively strong Coulomb interaction between Li and F atoms. 1-x The transmission trajectory in the VO3 structure.
[0073] Li 1-x VO3 and two different Li 1-x VO 3-ay F ay The energy distribution of lithium-ion transport in the structure is as follows Figure 6 As shown, the significant trend of the transport barrier demonstrates the importance of the optimal F concentration for achieving the lowest transport barrier. In Li 1-x In the VO3 structure, a transport barrier height exceeding 0.64 eV has been found, which is highly consistent with the experimental activation energy of 0.69 eV. Li 1-x VO 3-y F y The structure exhibits a minimum transport barrier of 0.13 eV, consistent with the experimental activation energy of 0.11 eV from the LVO-F-313 film. The significant difference in activation energy may be attributed to the affinity for lithium ions caused by the localized electrons from the F doping.
[0074] The slight difference between the experimental activation energy and the theoretical activation energy may be attributed to the difference in crystallinity, specifically the difference between the experimentally tested amorphous LVO-F-313 thin film and the crystalline Li used in the NEB calculations. 1-x VO 3-y F y Differences in crystallinity between supercells. (Compared to Li) 1-x VO 3-y F y Compared to its structure, Li 1-x VO 3-2y F 2y The structure exhibits a higher barrier height of 0.25 eV. This suggests that excessive F doping may lead to slow lithium-ion transport.
[0075] CI-NEB calculations support an optimal F concentration close to 1.7%, consistent with experimental results. However, these LiVO3-related structures in the computational study may not perfectly reflect the structure of the LVO-F-aba film.
[0076] B3) Conclusion
[0077] In summary, this work successfully demonstrates that controllable intrinsic fluorine doping leads to improved electronic and ionic conductivity in F-doped LVO coatings prepared by ALD. LVO-F functional coatings may not only protect the cathode / electrolyte interface but also improve charge transport, effectively addressing the poor conductivity problem of oxide coatings. Previous studies have proposed that LVO-F-313 films with optimal F doping concentration exhibit conductivity of 0.4%. With the lowest ASR value and an activation energy of 0.11 eV, it ranks among the best ALD coatings to date in terms of both electronic and ionic conductivity. DFT calculations further support the improved electronic and ionic conductivity observed in the LVO-F-313 film through the reduction of the band gap and the electron localization responsible for enhancing lithium-ion conductivity. Furthermore, NEB calculations reveal a significant reduction in the activation energy for lithium-ion transport at 1.7 atomic% F, consistent with experimental findings. We anticipate that hybrid conductive coatings will become more important in next-generation batteries, where the realization of uniform coatings will be increasingly crucial. A uniform LVO-F barrier layer combined with improved electron-ion hybrid conductivity can open new avenues for improving battery performance and durability without sacrificing charge transport across the interface with the cathode material.
[0078] B4) Method
[0079] B4a) Deposition of LVO and fluorine-doped LVO (LVO-F)
[0080] All LVO and LVO-F films were prepared in the Oxford FlexAL PEALD (Plasma Enhanced ALD) system. A complete ALD cycle for LVO-F deposition consisted of films sandwiched between LiVO and F. x The LiF ALD sub-cycles between the ALD sub-cycles constitute a structure. Here, LiVO x ALD sub-cycle by LiO x ALD sub-loop and VO x ALD subcycle composition. Lithium tert-butoxide (LiO) t Bu, Strem Chemicals (98%) and triisopropoxyvanadium oxy(V) (VTIP, Strem Chemicals, 98%) bubblers were used as LiVO4 bubblers. x The precursors in the ALD process are maintained at 150°C and 40°C, respectively. LiO t The precursor dose times for Bu and VTIP were fixed at 740 ms and 540 ms, respectively. A 10 s oxygen plasma was used as the LiVO2 plasma. xThe co-reactant in the ALD subcycle is at a flow rate of 30 standard cubic centimeters per minute (SCCM). The plasma is generated using oxygen (99.993%) from an inductively coupled plasma (ICP) source operating at 300 W. For the LiF ALD subcycle, LiO... t Bu and titanium fluoride (TiF4, Strem Chemicals, 98%) were selected as the precursor and reactant, respectively. LiO t Bu was introduced before the TiF4 injection, which lasted 100 ms. The TiF4 reactant vessel was maintained at 90°C, and the substrate temperature was fixed at 200°C for all deposition processes. Between each precursor and reactant injection, the manifold and ALD chamber were purged with 99.999% Ar for 20 seconds to avoid any cross-contamination from the precursors during deposition. We noted that the F content in the film did not originate from contamination in the ALD chamber, but was controlled solely by the number of ALD subcycles.
[0081] These LiVO x The ALD subcycle may be repeated 'a' times, while the LiF ALD subcycle may be replicated 'b' times. The values of a and b may vary between 1 and 6. For example, LVO-F-313 film represents LiVO where a single LiF ALD subcycle is repeated three times. x The block is sandwiched in the middle. The number of ALD sub-cycles of the original LVO was intentionally set to 18 to obtain a film thickness comparable to other LVO-F films.
[0082] B4b) Material Characterization
[0083] In all characterizations, all LVO and LVO-F films were deposited on p-type boron-doped Si(100) wafers. Film composition was determined by X-ray photoelectron spectroscopy (XPS) using the PHIVRSAprobe 4 instrument at the Stanford Nanoscale Shared Facility (SNSF) with Al Kα radiation as the light source and the PHI instrument-specific relative sensitivity factor. All films were sputtered with single atoms of Ar to remove surface carbon contamination. Furthermore, all XPS spectra were calibrated using the determinate carbon peak at 248.8 eV.
[0084] Thin film thicknesses were determined using a JA Woollam M2000 spectroellipsometer at the Stanford Shared Facility (SNF) with incident angles of 65°, 70°, and 75°, employing a general oscillator layer model with Tauc-Lorentz functions, adapted for oxides, provided by JA Woollam. The relative thicknesses of silicon and its native oxide layer were incorporated into the model at values of 1 mm and 16 nm, respectively.
[0085] The structure of the LVO-F thin film was investigated using grazing incidence X-ray diffraction (GIXRD) with a SNSF PANalytical X'Pert2 X-ray diffractometer and Cu K radiation as the light source. The thin film sample was supported on a glass substrate with an incident angle of 6.5°.
[0086] Transmission electron microscopy (TEM) images were obtained using a Thermo Fisher Spectra dual-corrected TEM from SNSF at an accelerating voltage of 300 kV. For TEM analysis, commercial LMO powder (MTI) was loaded onto a TEM grid, and then an LVO-F thin film was directly deposited onto the LMO powder.
[0087] B4c) Electrical Testing
[0088] Electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV) measurements were performed using a Solartron ModuLab XMECS system. Two platforms were used for EIS measurements: a highly boron-doped p-type silicon platform and an LMO platform. To characterize the intrinsic properties of the film without an electrode layer, a highly boron-doped p-type silicon (hPSi platform) with an aluminum back coating was used as the bottom electrode in temperature-varying EIS measurements. The charge transfer resistance was used to plot the Arrhenius plot; this resistance was obtained by subtracting the ohmic resistance from the total resistance, corresponding to the diameter of the semicircle in the Nyquist plot. The hPSi platform was also used at a scan rate of 100 mV. s -1 LSV test.
[0089] The LMO platform was chosen as a proof-of-concept to investigate the charge transfer properties of thin films with electrode layers. The platform consists of LMO layers deposited on platinum (Pt) top and bottom electrodes. Both the Pt electrodes and LMO layers were deposited using RF (radio frequency) sputtering. The charge transfer resistance of the thin film was selected for ASR calculations.
[0090] The conductivity (σ) of all thin films, including bare LMO, is determined by Equation 3:
[0091] L is the film thickness measured by ellipsometry, R is the charge transfer resistance, and A is the geometric area of the top Pt electrode.
[0092] The activation energy is extracted from the slope of the Arrhenius diagram using the Arrhenius equation:
[0093] In the formula, σ0 is the pre-exponential factor, E a For activation energy, is Boltzmann's constant, and T is the absolute temperature.
[0094] All electrical tests were performed in at least four different regions of the sample to ensure repeatability. The top electrode mask has a geometric area of 700 × 700 μm. 2 .
[0095] B4d) Density Functional Theory (DFT) Calculation
[0096] All DFT calculations were performed using the QuantumATK atomic simulation software package. All electron calculations were performed using a generalized gradient approximation (GGA)-Perdew-Burke-Ernzerhof (PBE) functional combined with a grid-based projected fused wave (GPAW) pseudopotential. The calculations employed a plane-wave basis set with a cutoff energy of 680 eV and a broadening of the Fermi-Dirac distribution at 300 K. Iterations were performed on the self-consistent field (SCF) loop until the total energy difference reached 10. -5 eV was used to compute solutions to the Cohen-Shen Lüjiu equation. All crystal structures were optimized using the Restricted Broyden-Fletcher-Goldfarb-Shannon algorithm (LBFGS) integrated into the QuantumATK software package.
[0097] The monoclinic lithium vanadate (LiVO3) structure, which has the closest stoichiometry to the LVO3 film deposited by ALD, was chosen as the basis for the calculations. This monoclinic LiVO3 structure is based on the Materials Project (MP-19373). The LiVO3 unit cell contains two Wyckoff lithium sites and three Wyckoff oxygen sites. The material structure in this work is based on a supercell approach. Prior to supercell construction, the atomic coordinates of the unit cell were first determined under periodic boundary conditions below 0.01 eV. Å -1 Under the atomic force convergence threshold, optimization was performed using the Monkhorst-Parker method with a 5×5×5 k-point grid. Subsequently, a 1×1×3 supercell structure was constructed under periodic boundary conditions. This was to generate the F-doped LVO structure (LiVO). 3-y F y In this study, a single F atom replaces one of the three oxygen sites in the optimized LiVO3 structure. Considering the total of 60 atoms in the supercell structure, this corresponds to a doping concentration of approximately 1.7 atomic percent. This work investigated LiVO3 structures with different F doping sites. 3-y F y Supercell structure, and select the most stable LiVO4. 3-y F y The supercell is used for subsequent calculations. This LiVO 3-y F y The atomic coordinates of the supercell structure are also at 0.015 eV. Å -1Optimization was performed under the force convergence threshold. The reciprocal momentum space was discretized using a 6×6×4 k-point Monkhorst-Parker grid offset to the Γ point. A Gaussian broadening of 0.1 eV was applied to the calculation of projected density of states (PDOS), band structure, and partial electron density.
[0098] Structures with a single lithium vacancy employ optimized LiVO3 or LiVO3. 3-y F y The structures are generated and further relaxed using the same force threshold and k-point grid. These structures with a single lithium vacancy are denoted as Li... 1-x VO3 and Li 1-x VO 3-y F y LiVO3 and LiVO were considered. 3-y F y Multiple lithium vacancy sites in the supercell. The formation energy of a lithium vacancy is calculated by the following formula:
[0099] Among them, E(V) Li () is LiVO3 or LiVO with lithium vacancies 3-y F y The total energy of the supercell, E(primary), is LiVO3 or LiVO3 without lithium vacancies. 3-y F y Total energy of the supercell, μ Li Let n be the chemical potential of lithium, and n be the chemical potential of lithium. Li This represents the number of lithium vacancies.
[0100] B4e) Calculation of the micro-motion elastic band (NEB)
[0101] To elucidate the effect of F doping on lithium-ion transport in the LVO host structure, a picture-dependent pair potential was used to target Li. 1- x VO 3-y and Li 1-x VO 3-ay F ay A ramp-image NEB (CI-NEB) was implemented in the supercell. Considering the size of the supercell structure, each specific value of "a" corresponds to 0, 1.7%, and 3.4% of F atoms, respectively. Among the possible NEB pathways, a trajectory from the second lithium vacancy site to the first lithium vacancy site was selected to allow the lithium ion to jump to another LiWyckoff site, as described elsewhere. This satisfies 0.07 eV. Å -1 The lithium-vacancy structure with force tolerance was selected as the start and end points of the NEB trajectory. The maximum diffusion distance of lithium ions in each image was fixed at 0.5 Å. Subsequently, 10 Å was used. -5The energy tolerance of eV and 0.07 eV Å -1 The force tolerance is used to optimize the NEB trajectory.
Claims
1. A lithium battery, comprising: anode; cathode; Electrolytes; as well as A barrier layer disposed on at least one of the cathode and anode; The barrier layer contains ternary lithium oxide grown by ALD (atomic layer deposition); In this process, the ternary lithium oxide grown by ALD is doped with fluorine during the ALD growth period.
2. The lithium battery according to claim 1, wherein, The barrier layer has a mixed conductivity provided by both electrons and ions.
3. The lithium battery according to claim 1, wherein, The barrier layer allows lithium-ion transport.
4. The lithium battery according to claim 3, wherein, The ionic conductivity of the barrier layer is 10. -6 S / cm to 10 2 Within the range of S / cm.
5. The lithium battery according to claim 3, wherein, The electronic conductivity of the barrier layer is 10. -8 S / cm to 10 2 Within the range of S / cm.
6. The lithium battery according to claim 1, wherein, The ternary lithium oxide grown by ALD comprises a Li-MO composition, wherein M is selected from the group consisting of Ti, Nb, V, W, Mn, Mo, Ta, La, Co, and Ni.
7. The lithium battery according to claim 1, wherein, The barrier layer is disposed on the cathode and on the anode.
8. The lithium battery according to claim 1, wherein, The fluorine atomic fraction of the ternary lithium oxide grown by ALD is from 0.5 atomic% to 6 atomic%.
9. The lithium battery according to claim 8, wherein, The fluorine atomic fraction of the ternary lithium oxide grown by ALD is from 1 atom% to 3 atoms.
10. The lithium battery according to claim 1, wherein, The ternary lithium oxide grown by ALD is formed by deposition through repeated ALD cycles, the ALD cycle including a lithium fluoride cycle sandwiched between lithium vanadate sub-cycles.
11. The lithium battery according to claim 1, wherein, The thickness of the barrier layer is 3 nm to 20 nm.
12. The lithium battery according to claim 1, wherein, The cathode comprises one or more materials selected from the group consisting of: LiMn2O4 (spinel), LiFePO4 (olivine), LiCoO2 (layered), and LiNi. x Mn y Co z O2 (layered).
13. The lithium battery according to claim 1, wherein, The anode comprises one or more materials selected from the group consisting of: silicon, graphite, Li4Ti5O. 12 And lithium metal.
14. The lithium battery according to claim 1, wherein, The electrolyte comprises one or more materials selected from the group consisting of LiPON and Li7La3Zr2O. 12 .
15. The lithium battery according to claim 1, wherein, The electrolyte is a liquid or solid electronic insulator with an ionic conductivity of 10. -8 S / cm to 10 -1 Within the range of S / cm.